Intra‐left ventricular flow dynamics in patients with preserved and impaired left ventricular function: Analysis with 3D cine phase contrast MRI (4D‐Flow). Issue 6 (17th May 2016) - Suwa, Kenichiro; Saitoh, Takeji; Takehara, Yasuo; Sano, Makoto; Saotome, Masao; Urushida, Tsuyoshi; Katoh, Hideki; Satoh, Hiroshi; Sugiyama, Masataka; Wakayama, Tetsuya; Alley, Marcus; Sakahara, Harumi; et al.
Abstract : Purpose: To examine how left ventricular (LV) volume and function affect flow dynamics by analyzing 3D intra‐LV vortex features using 4D‐Flow. Materials and Methods: Twenty‐one patients with preserved (LVEF > 60%) and 14 with impaired LV function (LVEF < 40%) underwent 4D‐Flow (at 3T). Results: In patients with preserved LV function, the intra‐LV vortices developed in both the early and late diastolic phases. The shift of inflow vectors at the basal LV toward the posterior‐lateral side of the LV and the mid‐ventricular turn of inflow vectors toward the LV outflow could explain clearer vortex formation in the late diastolic phase. In patients with impaired LV function, the intra‐LV vortices during the diastolic phase located at the more apical LV were larger and more spherically shaped. Both the distance to the vortex core and the vortex area correlated significantly with LV end‐diastolic volume ( r = 0.66 and 0.73), LVEF ( r = –0.74 and –0.68), LV sphericity index ( r = –0.60 and –0.65), and peak filling rate ( r = –0.61 and –0.64), respectively ( P < 0.01). The intra‐LV vortices developed during the systolic phase in 10 cases. In those, some of the particles at the apical LV rotated within the LV, whereas in patients with preserved LV function, all of the particles were directed straight to the ascending aorta with accelerated flow velocity (256.8 ± 120.2 cm/s vs. 414.3 ± 88.2 cm/s, P < 0.01). Conclusion: Vortex formation during the diastolic phase may be critical for both LV filling and ejection. 4D‐Flow showed the 3D alterations of intra‐LV flow dynamics by LV dilatation and dysfunction in a noninvasive and comprehensive manner. J. Magn. Reson. Imaging 2016;44:1493–1503.